Callitriche stagnalis Scopoli 1772 - Lansdown, Richard V.; Hassemer, Gustavo (Zenodo, 2021)
20. Callitriche stagnalis Scopoli (1772: 251) Type: — UNITED KINGDOM. CARDIGANSHIRE: Aberleri Fields, Borth, Cards 22/61209160, 20 July 1998, A.O. Chater s.n. (neotype [designated by Lansdown 2006b: 108] NMW!). Description: —Stem and leaf scales present. Leaf bases connate. Lingulate leaves very rare, usually lacking, expanded submerged or floating leaves variable, from broadly parallel-sided, through obovate spathulate to almost circular, 2.7–21.4(–21.7) × 1.4–8.3 mm, petiole 0.7–6.5(–7.5) mm, venation simple or complex with numerous loops and anastomosing veins, the apical leaves forming a floating rosette, leaves of terrestrial plants narrowly elliptic 2.6–4.4 × 1.6–3.3 mm, petiole 0.8–2.1 mm. Flowers usually solitary. Bracts falcate, persistent 0.6–2.6(–2.9) mm. Styles erect, becoming recurved in fruit, ≤ 6 mm. Filaments erect, becoming recurved and continuing to grow after dehiscence; ≤ 16.2 mm; anthers reniform, 0.3–0.9 mm diameter; pollen yellow. Fruit not strumose, subsessile or occasionally very shortly-pedicellate, ± as wide as high, greyish when mature, 1.1–1.8 × 1.1–2.0 mm, winged throughout. Illustrations: —figures on pages 81 and 83 in Lansdown (2008); Figure 5 (i). Distribution: — Callitriche stagnalis is native to Europe, from the Azores to Iceland and east to the western side of the Ural Mountains in Russia (Lansdown 2006a). It also occurs as an alien (naturalised) in North America (Philbrick et al. 1998), Australia (Orchard 1980), New Caledonia and New Zealand (Mason 1959). Two specimens are known from South America, one from Biobío Province in Chile and one from the Falkland Islands. Notes: — Callitriche stagnalis was reported in error from Brazil, but recognised as occurring as a non-native in Chile and the Falkland Islands (Lansdown & Hassemer 2018). It can be distinguished from all other Callitriche species in the region bY the large fruit (> 1 mm diameter), long stYle (≤ 6 mm long) and long filament (≤ 16 mm long). Conservation status: — Callitriche stagnalis is classed as Least ...